University student's engagement: Development of the University Student Engagement Inventory (USEI) - Maroco, João; Maroco, Ana Lúcia; Bonini Campos, Juliana Alvares Duarte [UNESP]; Fredricks, Jennifer A. (Springer Nature, 2016)
Student engagement is a key factor in academic achievement and degree completion, though there is much debate about the operationalization and dimensionality of this construct. The goal of this paper is to describe the development of an psycho-educational oriented measure - the University Student Engagement Inventory (USEI). This measure draws on the conceptualization of engagement as a multidimensional construct, including cognitive, behavioural and emotional engagement. Participants were 609 Portuguese University students (67 % female) majoring in Social Sciences, Biological Sciences or Engineering and Exact Sciences. The content, construct and predictive validity, and reliability of the USEI were tested. The validated USEI was composed of 15 items, and supported the tri-factorial structure of student engagement. We documented evidence of adequate reliability, factorial, convergent and discriminant validities. USEI's concurrent validity, with the Utrecht Work Engagement Scale-Student Survey, and the predictive validity for self-reported academic achievement and intention to dropout from school were also observed.
Keywords: Academic achievement; Scale construction; School dropout; University students' engagement